Photosensitized Oxidation of Sulfides: Discriminating between the Singlet-Oxygen Mechanism and Electron Transfer Involving Superoxide Anion or Molecular Oxygen - Bonesi, Sergio M.; Manet, Ilse; Freccero, Mauro; Fagnoni, Maurizio; Albini, Angelo (Chemistry : a European journal, 2006)
The oxidation of diethyl and diphenyl sulfide photosensitized by dicyanoanthracene (DCA), N‐methylquinolinium tetrafluoroborate (NMQ+), and triphenylpyrylium tetrafluoroborate (TPP+) has been explored by steady‐state and laser flash photolysis studies in acetonitrile, methanol, and 1,2‐dichloroethane. In the Et2S/DCA system sulfide‐enhanced intersystem crossing leads to generation of 1O2, which eventually gives the sulfoxide via a persulfoxide; this mechanism plays no role with Ph2S, though enhanced formation of 3DCA has been demonstrated. In all other cases an electron‐transfer (ET) mechanism is involved. Electron‐transfer sulfoxidation occurs with efficiency essentially independent of the sulfide structure, is subject to quenching by benzoquinone, and does not lead to Ph2SO cooxidation. Formation of the radical cations R2S.+ has been assessed by flash photolysis (medium‐dependent yield, dichloroethane≫CH3CN>CH3OH) and confirmed by quenching with 1,4‐dimethoxybenzene. Electron‐transfer oxidations occur both when the superoxide anion is generated by the reduced sensitizer (DCA.−, NMQ.) and when this is not the case (TPP.). Although it is possible that different mechanisms operate with different ET sensitizers, a plausible unitary mechanism can be proposed. This considers that reaction between R2S.+ and O2.− mainly involves back electron transfer, whereas sulfoxidation results primarily from the reaction of the sulfide radical cation with molecular oxygen. Calculations indeed show that the initially formed fleeting complex RS2+⋅⋅⋅OO. adds to a sulfide molecule and gives strongly stabilized R2SO.+OSR2 via an accessible transition state. This intermediate gives the sulfoxide, probably via a radical cation chain path. This mechanism explains the larger scope of ET sulfoxidation with respect to the singlet‐oxygen process. Sensitization of sulfides by electron transfer involves different paths from the radical ion pair, either via the sensitizer triplet 3Sens (and thus via 1O2) or via O2.−. Experimental and computational evidence suggests, however, that a main path to oxidation products involves trapping of the sulfide radical cation by molecular oxygen (see scheme).